The Effect of Health Education on Menstruation with Audiovisual Media on Anxiety Levels in Facing Menarche in Elementary School Students 1 and 2 Ngadimulyo - Siti Rohana; Dhita Aulia Octaviani; Heny Rosiana (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2022)
Menarche is the first menstruation which is a sign that a teenage girl has reached the maturity of her sexual function. Anxiety is influenced by several factors, one of which is knowledge, with ignorance of information it can cause anxiety. Health education with audiovisual media involves the senses of sight and hearing to receive the information provided, so that it will be more easily accepted. The purpose of this study was to determine the effect of health education on menstruation on the level of anxiety in dealing with menarche in students of SD Negeri 1 and 2 Ngadimulyo. This research was a quantitative research, used the one-group pre-post test design method. The research population was 38 female students, with the sample collection technique used non-random sampling technique, namely the total sample of 38 respondents. Anxiety measuring instrument used in this study using the ZSAS questionnaire. The results showed that the level of anxiety before the intervention there were 26 (68.4%) respondents experienced mild anxiety and 12 (31.6%) respondents experienced moderate anxiety, while after being given the intervention there were 36 (94.7%) respondents experienced mild anxiety and 2(5.3%) respondents experienced moderate anxiety, and the results of the Wilcoxon statistical test obtained a p-value of 0.000 or 0.5, which means that there is an effect of health education about menstruation on the level of anxiety in dealing with menarche in students of SD Negeri 1 and 2 Ngadimulyo. It is hoping that the existence of health education about menstruation through school business activities can increase the readiness of students in facing menarche.